Cultivating a Leadership Pipeline: Using a Real Options Lens to Understand Executives’ Strategic Staffing Decisions - Campion, Michael C.; Campion, Emily D.; Campion, Michael A.; Bauer, Talya N. (Organization Science, 2023)
This paper adapts real options theory to explain how executives create and maintain real options portfolios within leadership pipelines. Hypotheses flowing from our theorizing predict that executives often make seemingly risky staffing decisions for leaders who occupy stepping-stone positions. Focusing on their option (future potential) rather than project (current productivity) value, executives laterally transfer leaders in stepping-stone positions frequently, despite it resulting in lower short-term job performance, but often promote these leaders at lower levels of performance and sooner. Once leaders are promoted to destination positions where they may stay indefinitely, executives tend to transfer high-performing leaders more often but not when they are still improving the effectiveness of their current unit. We present evidence suggesting that executives make these decisions to improve other units and maintain a flexible system, possibly recapturing previous investments in developing those leaders. We provide empirical support for our hypotheses using eight years of data in a large retail organization (n = 25,004) where executives overseeing thousands of units made internal mobility decisions. These findings refine real options theory, show that it explains these phenomena better than existing theories, and provide important and immediately usable practical implications for executives. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1608 .